THE ROLE OF ACTIVATION OF THE SYMPATHETIC NERVOUS SYSTEM IN THE PATHOGENESIS OF ARTERIAL HYPERTENSION AND THE CHOICE OF A METHOD FOR THE TREATMENT OF ARTERIAL HYPERTENSION - A. V. Rozanov; Yu. V. Kotovskaya; O. N. Tkacheva (Евразийский Кардиологический Журнал)
The basis for the successful treatment of any disease is a clear understanding of its cause, the mechanisms of its development, and their relationship to symptoms. The article considers one of the links in the pathogenesis of arterial hypertension - an increase in the activity of the sympathetic nervous system, describes the main methods for detecting hypersympathicotonia, approaches to the selection of drug therapy.